Bacteria Associated with Acute Oak Decline: Where Did They Come From? We Know Where They Go - Daniel Maddock; Carrie Brady; Sandra Denman; Dawn Arnold (Microorganisms, 2023)
Acute oak decline is a high-impact disease causing necrotic lesions on the trunk, crown thinning and the eventual death of oak. Four bacterial species are associated with the lesions—Brenneria goodwinii, Gibbsiella quercinecans, Rahnella victoriana and Lonsdalea Britannica—although an epi-/endophytic lifestyle has also been suggested for these bacteria. However, little is known about their environmental reservoirs or their pathway to endophytic colonisation. This work aimed to investigate the ability of the four AOD-associated bacterial species to survive for prolonged periods within rhizosphere soil, leaves and acorns in vitro, and to design an appropriate method for their recovery. This method was trialled on field samples related to healthy and symptomatic oaks. The in vitro study showed that the majority of these species could survive for at least six weeks within each sample type. Results from the field samples demonstrated that R. victoriana and G. quercinecans appear environmentally widespread, indicating multiple routes of endophytic colonisation might be plausible. B. goodwinii and L. britannica were only identified from acorns from healthy and symptomatic trees, indicating they may be inherited members of the endophytic seed microbiome and, despite their ability to survive outside of the host, their environmental occurrence is limited. Future research should focus on preventative measures targeting the abiotic factors of AOD, how endophytic bacteria shift to a pathogenic cycle and the identification of resilient seed stock that is less susceptible to AOD.